Penerapan Model Pembelajaran Inkuiri (Inquiry Learning) untuk Meningkatkan Hasil Belajar Siswa di SD Gmim VI Tomohon - Ester, Kartini; Tampombebu, Olivia Inriana; Mauru, Lisa Aprisilia; Batseran, Hendrikus; Tambayong, Jichela Rensel (Peneliti.net, 2023)
This research aims to improve student learning outcomes by implementing the inquiry learning model at SD GMIM VI Tomohon with the topic of Length Measurement being discussed. This type of research is qualitative research with data collection techniques through student observations in the classroom. The subjects of this research were 20 class II students. The results of this research show that the application of the inquiry learning model can improve students' mathematics learning outcomes. Improving student learning outcomes can be done by conveying learning objectives, providing problems related to concepts, providing practice questions, and providing guidance to students who have difficulty by discussing practice questions.